The accompaniment in the Tunisian entrepreneurial ecosystem - ABDENNADHER, Sarhan; BOUDABBOUS, Sami (Journal of Entrepreneur, Business and Management, 2025)
The development of countries is dependent on certain political conditions, but also and above all socio-economic ones. At this level, entrepreneurship, through its different forms, plays a key role. In this sense, in Tunisia, the public authorities have opted to encourage private initiative and have been engaged since the mid-1980s in a program aimed at creating a favorable entrepreneurial ecosystem.Indeed, entrepreneurship can only be stimulated by meeting the needs of entrepreneurs at different levels of the entrepreneurial process. It is in this context that this contribution is made, the objective of which is to explore, through qualitative exploratory research, the accompaniment of entrepreneurs in the Tunisian entrepreneurial ecosystem. The results of our study reveal that, although the actors of the Tunisian entrepreneurial ecosystem play an undeniable role in promoting and supporting entrepreneurial initiatives, several elements suggest that the ecosystem as a whole has not yet managed to generate a fully coherent and efficient dynamic. Indeed, there is an urgent need to improve the interconnection between the different actors of the ecosystem, in order to create a real value chain for entrepreneurial initiatives.